THE PROTOPLANETARY SYSTEM FORMATION AS A RESULT OF THE MERGING OF CLOSE BINARY STAR CONSISTING OF THE LOW MASS PRE-MS STARS - Sirotkin, F. V.; Karetnikov, V. G. (Одеські астрономічні публікації, 2017)
The mechanism of protoplanetary system formation as a result of a merge of binary star consisting of the low mass (0.5-1M⊙) pre-MS stars is considered. During the merging the more massive component is destroyed. The substance of the destroyed component forms spiral gaseous arm and circumstellar disk. The protoplanetary embryos (clouds) with masses about 2-5 Mj are forming as the result of division of the spiral arm. The rotation of the circumstelar disk, clouds and star are in plane. The formed clouds are on the eccentric (e > 0.3) orbits.